MRSA compendium of epidemiology, transmission, pathophysiology, treatment, and prevention within one health framework - Shoaib, Muhammad; Aqib, Amjad Islam; Muzammil, Iqra; Majeed, Noreen; Bhutta, Zeeshan Ahmad; Kulyar, Muhammad Fakhar-e-Alam; Fatima, Mahreen; Zaheer, C-Neen Fatima; Muneer, Afshan; Murtaza, Maheen; Kashif, Muhammad; Shafqat, Furqan; et al. (Frontiers in Microbiology, 2023)
Staphylococcus aureus is recognized as a commensal as well as an opportunistic pathogen of humans and animals. Methicillin resistant strain of S. aureus (MRSA) has emerged as a major pathogen in hospitals, community, and veterinary settings that compromises public health and livestock production. MRSA basically emerged from MSSA after acquiring the SCCmec element through gene transfer containing the mecA gene responsible for encoding PBP-2α. This protein renders MRSA resistant to most β-lactam antibiotics. The continuously increasing prevalence and transmission of MRSA in hospitals, community, and veterinary settings pose a major threat to public health. Furthermore, the high pathogenicity of MRSA due to a number of virulence factors produced by S. aureus along with antibiotic resistance help to breach the immunity of the host and is responsible for causing severe infections in humans and animals. The clinical manifestations of MRSA consist of skin and soft tissue infection to bacteremia, septicemia, toxic shock, and scalded skin syndrome. Moreover, due to the increasing resistance of MRSA to a number of antibiotics, there is a need to approach alternatives ways to overcome economic as well as human losses. This review is going to discuss various aspects of MRSA starting from emergence, transmission, epidemiology, pathophysiology, disease patterns in hosts, and novel treatment & control strategies.